RELATIONS BETWEEN ASSESSMENT AGENTS OF SOCIAL COMPETENCE IN PREADOLESCENTS: TEACHERS, PEERS AND SELF-REPORTS - Trianes, Mª Victoria; Blanca Mena, María José; Muñoz, Angela; García, Belén; Cardelle-Elawar, María; Infante, Lidia (Anales de Psicología / Annals of Psychology, 2002)
This work aims to analyse the relations among the results of the assessment of social skills and social behaviour problems coming from different sources: teachers, peers and self-reports. Data obtained after regression analysis over the variables yielded by factor analysis show that teachers and self-report agree in the assessment of positive assertive behaviour and in the negative assessment of aggressive/impulsive behaviour. Peers assessment and self-reports coincide in the association of impulsive/ aggressive behaviour with low peer acceptance. Peers´ and teacher’s assessment correlate in the case of skilled students. Finally, peer acceptance is also correlated to inhibition assessed by teacher, which allows us to point out the ambiguity of the category "inhibition" in the school context.